Factors affecting pharmacy engagement and pharmacy customer devotion in community pharmacy: A structural equation modeling approach - Nitadpakorn S; Farris KB; Kittisopee T. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Background: The concept of customer engagement and devotion has been applied in various service businesses to keep the customers with business However, a limited number of studies were performed to examine the context of customer engagement and devotion in pharmacy business which focus on the impact of customer perceptions about pharmacists, perceived quality of pharmacy structure, medication price strategy on pharmacy engagement and pharmacy customer devotion in a pharmacy providing pharmaceutical care to the customers. Objective: This study aimed to assess a conceptual model depicting the relationships among customer perceptions about pharmacists, pharmacy quality structure, medication price, customer engagement, and customer devotion. And also aimed to assess and measure if there is a direct or indirect relationship between these factors. Methods: A quantitative study was conducted by using self-administered questionnaires. Two hundred and fifty three customers who regularly visited the pharmacy were randomly recruited from a purposively selected 30 community pharmacies in Bangkok. The survey was completed during February to April 2016. A structural equation model (SEM) was used to assess the direct and indirect relationships between constructs. Results: A total of 253/300 questionnaires were returned for analysis, and the response rate was 84%. Only perceptions about pharmacist in customers receiving professional pharmacy services was statically significant regarding relationship with pharmacy engagement (beta=0.45). Concurrently, the model from empirical data fit with the hypothetical model (p-value = 0.06, adjusted chi-square (CMIN/DF)=1.16, Goodness of Fit Index (GFI)=0.93, Comparatively Fit Index (CFI)=0.99, and Root Mean Square Error Approximation (RMSEA)=0.03). Conclusion: The study confirmed the indirect positive influence of customer perceptions about pharmacist on pharmacy customer devotion in providing pharmacy services via pharmacy engagement It was customer perceptions about pharmacist that influenced customer retention, positive word of mouth and constructive advice to pharmacies, not quality of pharmacy structure and medication price. To create a long term impact on community pharmacy business, pharmacist is the key success factor.